Several Guaranteed Descent Conjugate Gradient Methods for Unconstrained Optimization - San-Yang Liu; Yuan-Yuan Huang (Journal of Applied Mathematics)
This paper investigates a general form of guaranteed descent conjugate gradient methods which satisfies the descent condition gkTdk≤-1-1/4θkgk2  θk>1/4 and which is strongly convergent whenever the weak Wolfe line search is fulfilled. Moreover, we present several specific guaranteed descent conjugate gradient methods and give their numerical results for large-scale unconstrained optimization.